Odwzorowanie regionalnej struktury gospodarki - Domański, Ryszard (Wydział Prawa i Administracji UAM, 1969)
Economic geography begins very often its investigation at identification of expansion and spatial variation of the social and economical phenomena. Using some composing procedures it comes to the determination of regional patterns of some phenomena, but not all regional patterns of economic and social phenomena are equally interesting for economic geography. In farther phase of investigations it pays special attention to convergent patterns i. e. to those ones that seize more or less similar area or change in similar way. Convergence can be accidental or essential. The first case is not very interesting. To prove that the convergence is essential economic geography must show that the regional patterns of the phenomenon is in causal-consecutive connection with regional pattern of the other phenomenon, or that there exists a process (common cause) that has conditioned the convergence of both patterns. Thus, the essential (meaning) convergence occurs when the causal relations accompany the concomitance of various regional patterns. The proof of occurrence is a scientific problem, the solution of which enlarges our knowledge about regions and the way they are made productive. The paper presents a method of mapping regional structure of economy and . proves it on the example of the Konin - Łęczyca - Inowrocław Industrial District. It is an extension of earlier procedure applied to the examination of two regional patterns. The extension made it applicable to the examination of many regional patterns. Thus, we are able at present to map more complex structures of economy in regions.
Mapping of the Regional Structure of Economy